2020
DOI: 10.7717/peerj.9662
|View full text |Cite
|
Sign up to set email alerts
|

The Bayesian confidence intervals for measuring the difference between dispersions of rainfall in Thailand

Abstract: The coefficient of variation is often used to illustrate the variability of precipitation. Moreover, the difference of two independent coefficients of variation can describe the dissimilarity of rainfall from two areas or times. Several researches reported that the rainfall data has a delta-lognormal distribution. To estimate the dynamics of precipitation, confidence interval construction is another method of effectively statistical inference for the rainfall data. In this study, we propose confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“… Maneerat, Niwitpong & Niwitpong (2020) constructed Bayesian credible intervals for the difference between variances of delta-lognormal distributions. Yosboonruang, Niwitpong & Niwitpong (2020) proposed Bayesian credible intervals for measuring the difference between rainfall dispersions datasets for regions in Thailand. Thangjai, Niwitpong & Niwitpong (2020c) estimated Bayesian credible intervals for the means of normal distributions with unknown coefficients of variation.…”
Section: Introductionmentioning
confidence: 99%
“… Maneerat, Niwitpong & Niwitpong (2020) constructed Bayesian credible intervals for the difference between variances of delta-lognormal distributions. Yosboonruang, Niwitpong & Niwitpong (2020) proposed Bayesian credible intervals for measuring the difference between rainfall dispersions datasets for regions in Thailand. Thangjai, Niwitpong & Niwitpong (2020c) estimated Bayesian credible intervals for the means of normal distributions with unknown coefficients of variation.…”
Section: Introductionmentioning
confidence: 99%
“…2 together with the Akaike information criterion (AIC) and the Bayesian information criterion (BIC) indicate that the daily rainfall data from the three areas follow delta-lognormal distributions. Furthermore, many researchers have reported that rainfall data follow a delta-lognormal distribution ( Fukuchi, 1988 ; Shimizu, 1993 ; Yue, 2000 ; Kong et al, 2012 ; Maneerat, Niwitpong & Niwitpong, 2019a , 2020a , 2020b ; Yosboonruang, Niwitpong & Niwitpong, 2019b , 2020 ; Yosboonruang & Niwitpong, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For statistical inference, several methods for constructing confidence intervals for the CV and functions of the CV have been suggested ( e.g . Pang et al, 2005 ; Hayter, 2015 ; Nam & Kwon, 2017 ; Yosboonruang, Niwitpong & Niwitpong, 2018 , 2019a , 2019b , 2020 ; Yosboonruang & Niwitpong, 2020 ). However, since using the common CV of delta-lognormal distributions for statistical inference has not previously been reported, this has become our research interest as it is useful for measuring the dispersion in several independent data series, especially rainfall data.…”
Section: Introductionmentioning
confidence: 99%
“…Sangnawakij, Niwitpong & Niwitpong (2015) presented confidence intervals for the ratio of coefficients of variation of gamma distributions. Yosboonruang, Niwitpong & Niwitpong (2020) proposed confidence intervals for the difference between the coefficients of variation of delta-lognormal distributions. La-ongkaew, Niwitpong & Niwitpong (2009) constructed confidence interval for single coefficient of variation of Weibull distribution.…”
Section: Introductionmentioning
confidence: 99%